Deep eutectic solvents boosting solubilization and Se-functionalization of heteropolysaccharide: Multiple hydrogen bonds modulation. (15th May 2022) - Sun, Yaxu; Jia, Xiaoyan; Yang, Ru; Qin, Xiaojie; Zhou, Xiaoxue; Zhang, Hui; Kong, Weibao; Zhang, Ji; Wang, Junlong
Abstract: In this study, the favorable feasibility of deep eutectic solvents (DESs) in solubilization and functionalization of natural heteropolysaccharide was validated by experiments and density functional theory calculations. This revealed that choline chloride-based DES/DMSO (dimethyl sulfoxide) binary mixed solvents possessed more and stronger hydrogen bonding sites, facilitating the balance between disruption and reconstruction of hydrogen bonds within branched heteropolysaccharide from Artemisia sphaerocephala (PAS) and achieving efficient solubilization. Further, due to the full exposure and activation of polysaccharide hydroxyls, the efficiency of DES/DMSO-mediated novel Se-functionalization was substantially enhanced compared to the conventional selenylation methods. The derivative exhibited conversion to lower molecular mass with rigid solution conformation based on co-solvent effect and predominant acidic environment influence. This study offered a framework for exploring the potential of individualized polysaccharide functionalization by modulating DES constituents to achieve multiple controllabilities in terms of conversion efficiency and derivative structure. Graphical abstract: Unlabelled Image Highlights: Deep eutectic solvents disrupt H-bond networks of polysaccharides to solubilizate. Binary solvents exhibit multiple H-bonds-driven superior dissolving capacity. Adequate exposure and activation of hydroxyls deliver efficient functionalization.